An iron-base oxygen-evolution electrode for high-temperature electrolyzers - Kaifa Du; Enlai Gao; Chunbo Zhang; Yongsong Ma; Peilin Wang; Rui Yu; Wenmiao Li; Kaiyuan Zheng; Xinhua Cheng; Diyong Tang; Bowen Deng; Huayi Yin; et al. (Nature Communications, 2023)
A low-cost and efficient high-temperature oxygen evolution reaction electrode is a big challenge. Here, the authors report an iron-base electrode with an in situ formed lithium ferrite for enhanced stability and catalytic activity in molten carbonate and chloride salts and achieve kiloampere-scale electrolysis.